2009
DOI: 10.7153/mia-12-72
|View full text |Cite
|
Sign up to set email alerts
|

Weighted inequalities for a class of matrix operators: the case p ≤ q

Abstract: We prove a new discrete Hardy-type inequality A f q,u a i, j f j , a i, j 0 . Moreover, we study the problem of compactness of the operator A , and the dual result is stated. (2000): 26D10, 26D15, 47B37. Mathematics subject classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The inequalities (1) and (2) have been investigated for the case 0 < p, q < ∞ with a triangular matrix (a i,j ≥ 0 for 1 ≤ j ≤ i and a i,j = 0 for i < j) in [2][3][4][5] and the references given therein. However, these inequalities have not been studied for the case 0 < p ≤ q < ∞ and p ≤ 1.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inequalities (1) and (2) have been investigated for the case 0 < p, q < ∞ with a triangular matrix (a i,j ≥ 0 for 1 ≤ j ≤ i and a i,j = 0 for i < j) in [2][3][4][5] and the references given therein. However, these inequalities have not been studied for the case 0 < p ≤ q < ∞ and p ≤ 1.…”
Section: Applicationsmentioning
confidence: 99%
“…However, these inequalities have not been studied for the case 0 < p ≤ q < ∞ and p ≤ 1. Only, in 1991 G. Bennett [3] studied the inequality (1) for the this case with the identity matrix. He proved that the inequality (1) holds if and only if…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar problem for two-weighted integration operators on a semiaxis was solved by Bradley [5], Mazya and Rozin [21]. Later, these results were generalized for matrix operators and integration operators with different kernels (see, e.g., papers of Heinig and Andersen [1,14], Stepanov [30,31], Oinarov [23], Prokhorov and Stepanov [27], Stepanov and Ushakova [32], Rautian [28], Farsani [11], Oinarov, Persson and Temirkhanova [24], Okpoti, Persson and Wedestig [25,26], and the books [13,15,16]). In the case p = q = 2 Naimark and Solomyak [22] showed that the problem of estimating the norm of weighted integration operator on a regular tree with weights depending only on distance from the root can be reduced to a problem on estimating the norm of some weighted Hardy-type operator on a half-axis.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], estimate (3) has been studied under the assumption that there exist d ≥ 1 and a sequence of positive numbers {ω k } ∞ k=1 , and a non-negative matrix (b i,j ), where b i,j is almost non-decreasing in i and almost non-increasing in j, such that the inequalities…”
Section: Introductionmentioning
confidence: 99%